MULTIMORBIDITY BURDEN AND ADVERSE OUTCOMES IN OLDER ADULTS WITH HEART FAILURE. (11th November 2018) - Tisminetzky, M; Gurwitz, J; Fan, D; Reynolds, K; Smith, D; Sung, S; Murphy, T; Go, A
Abstract: Despite the high burden of multimorbidity among patients with heart failure (HF), few studies have examined the impact of multiple chronic conditions on important clinical outcomes by gender, age, and type of HF. We identified 114, 553 adults with HF and known left ventricular systolic function from five healthcare delivery systems and characterized the presence of 26 chronic conditions into quartiles of multimorbidity burden (0–4 morbidities, 5–6 morbidities, 7–8 morbidities, and ≥9 morbidities) based on data from electronic medical records. Outcomes included all-cause death, all-cause hospitalization, and HF hospitalization. Compared with 0–4 morbidities, adjusted hazard ratios (HR) for death among those with 5–6, 7–8, or 9 or more morbidities were: HR 1.27 (95% CI:1.24–1.31), HR 1.52 (1.48–1.57) and HR 1.92 (1.86–1.99), respectively. Compared with 0–4 morbidities, there was a graded adjusted risk of any-cause hospitalization for 5–6, 7–8, or 9 or more morbidities: HR 1.28 (1.25–1.30), HR 1.47 (1.44–1.50), and HR 1.77 (1.73–1.82). Similar findings were observed for HF-specific hospitalization in those with 5–6, 7–8, or 9 or more morbidities (vs. 0–4): HR 1.22 (1.19–1.26), HR 1.39 (1.34–1.44), and HR 1.68 (1.61–1.74). Comparable findings were observed by gender, age, and HF type (preserved, reduced, borderline HF) for the relationship between multimorbidity burden and outcomes, which was especially prominent among those <65 years. In a large community-based cohort of older adults with HF, increased burden of multimorbidity was independently associated with worse outcomes and should be considered in the management and clinical decision-making for patients with HF.